What Does It Mean to Reason Qualitatively? - Wałęga, Przemysław (Filozofia Nauki, 2015)
Qualitative reasoning methods have recently been used in a wide range of scien-tific disciplines, such as computer science, robotics, geography, physics, etc. Never-theless, it is still difficult to find an exhaustive explanation of what it means to reason qualitatively. In other words, there is hardly any clear definition of qualitative approach. In the paper, I try to explain this concept and describe some situations where it is applied.